Pantoprazole oral liquid liposomal formulation: Design and Characterization: Pantoprazole oral liquid liposomal formulation - Karami, Masoud Ali; Saeidi, Ali; Moghimipour, Eskandar (Iranian Journal of Pharmaceutical Sciences, 2024)
Pantoprazole (PPZ) is one of the proton pump inhibitors which is used to prevent the secretion of excess gastric acid in both adults and children. However, it is difficult to use in patients under 5 years of age or elderly patients due to the lack of appropriate liquid formulation. In this study, a liquid liposomal formulation of pantoprazole with improved physicochemical stability has been introduced to facilitate the drug administration in above mentioned patients. Lecithin and cholesterol in different ratios were used to prepare liposomes by the thin-layer hydration method. Optimization studies were performed to find the best formulation. Liposomes were examined for particle size, entrapment efficiency, and stability at ambient temperature. The morphology of liposomes was also investigated by scanning electron microscopy and light microscopy. The release rate of the drug from the liposomal formulation in the aqueous phase was monitored for 24 hours. The results showed more than 60% loading of pantoprazole into the liposomes. The particle size of liposomes decreased with increasing levels of lecithin. Analysis of variance showed a significant difference in drug release within 24 hours. The effects of time, temperature, and light on the apparent instability of the drug were restrained by liposomal formulation and the entrapped drug was more stable compared to the pantoprazole solution. The results of the present study demonstrated that the formulation of pantoprazole in liposomes could provide a new perspective for the treatment of gastric reflux.